Adsorption Behavior of Toxic Carbon Dichalcogenides (CX2; X = O, S, or Se) on β12 Borophene and Pristine Graphene Sheets: A DFT Study - Mahmoud A. A. Ibrahim; Amna H. M. Mahmoud; Gamal A. H. Mekhemer; Ahmed M. Shawky; Mahmoud E. S. Soliman; Nayra A. M. Moussa (Nanomaterials, 2022)
The adsorption of toxic carbon dichalcogenides (CX2; X = O, S, or Se) on β12 borophene (β12) and pristine graphene (GN) sheets was comparatively investigated. Vertical and parallel configurations of CX2⋯β12/GN complexes were studied herein via density functional theory (DFT) calculations. Energetic quantities confirmed that the adsorption process in the case of the parallel configuration was more desirable than that in the vertical analog and showed values up to −10.96 kcal/mol. The strength of the CX2⋯β12/GN complexes decreased in the order CSe2 > CS2 > CO2, indicating that β12 and GN sheets showed significant selectivity for the CSe2 molecule with superb potentiality for β12 sheets. Bader charge transfer analysis revealed that the CO2⋯β12/GN complexes in the parallel configuration had the maximum negative charge transfer values, up to −0.0304 e, outlining the electron-donating character of CO2. The CS2 and CSe2 molecules frequently exhibited dual behavior as electron donors in the vertical configuration and acceptors in the parallel one. Band structure results addressed some differences observed for the electronic structures of the pure β12 and GN sheets after the adsorption process, especially in the parallel configuration compared with the vertical one. According to the results of the density of states, new peaks were observed after adsorbing CX2 molecules on the studied 2D sheets. These results form a fundamental basis for future studies pertaining to applications of β12 and GN sheets for detecting toxic carbon dichalcogenides.